Do animals and furniture items elicit different brain responses in human infants? - Jeschonek, Susanna; Marinović, Vesna; Höhl, Stefanie; Elsner, Birgit; Pauen, Sabina (Brain & development, 2010)
One of the earliest categorical distinctions to be made by preverbal infants is the animate-inanimate distinction. To explore the neural basis for this distinction in 7-8-month-olds, an equal number of animal and furniture pictures was presented in an ERP-paradigm. The total of 118 pictures, all looking different from each other, were presented in a semi-randomized order for 1000ms each. Infants’ brain responses to exemplars from both categories differed systematically regarding the negative central component (Nc: 400-600ms) at anterior channels. More specifically, the Nc was enhanced for animals in one subgroup of infants, and for furniture items in another subgroup of infants. Explorative analyses related to categorical priming further revealed category-specific differences in brain responses in the late time window (650-1550ms) at right frontal channels: Unprimed stimuli (preceded by a different-category item) elicited a more positive response as compared to primed stimuli (preceded by a same-category item). In sum, these findings suggest that the infant’s brain discriminates exemplars from both global domains. Given the design of our task, we conclude that processes of category identification are more likely to account for our findings than processes of on-line category formation during the experimental session.
Gesehen am 24.08.2023